2023
DOI: 10.33490/jkm.v9i1.812
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review: The Role of Micronutrients (Fe, Zn, Iodine, Retinol, Folate) During Pregnancy

Abstract: Pregnant women are highly vulnerable to nutritional problems such as Chronic Energy Deficiency (CHD), deficiency of micronutrient intake (iron, zinc, and vitamin A intake), anemia, and Iodine Deficiency Disorder (IDD). Micronutrient deficiencies in pregnant women must be specifically prevented. A healthy and nutritionally balanced diet is essential for maternal and fetal health. The review study aimed to identify the role of micronutrients (Fe, Zn, Iodine, Vitamin A, and Folate) during pregnancy. The literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Several recent studies have reported that the immune system is affected by blood vitamin D levels, although the exact mechanism still requires a lot of further research. Initially, vitamin D was reported to play an important role in maintaining the health and strength of teeth and bones, but now, vitamin D is reported to be useful in the prevention of various degenerative diseases such as obesity, hypertension, diabetes mellitus, cancer, and many others (Hermawan, 2021;Al Rahmad, 2023;Manousaki & Richards, 2017;Maruotti & Cantatore, 2010;Sigmund, 2002;Vanlint, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported that the immune system is affected by blood vitamin D levels, although the exact mechanism still requires a lot of further research. Initially, vitamin D was reported to play an important role in maintaining the health and strength of teeth and bones, but now, vitamin D is reported to be useful in the prevention of various degenerative diseases such as obesity, hypertension, diabetes mellitus, cancer, and many others (Hermawan, 2021;Al Rahmad, 2023;Manousaki & Richards, 2017;Maruotti & Cantatore, 2010;Sigmund, 2002;Vanlint, 2013).…”
Section: Introductionmentioning
confidence: 99%